That Thing We Dreamed - (:unkn) unknown (My University, 2010)
The term " architecture " has historically been defined by and in relation to Europe. The same is true of the word " museum ". Both are understood to reference permanent structures created by highly trained specialists, according to set rules, for use to specific ends. This definition is exceedingly narrow. It excludes the overwhelming majority of structures encountered, historically and today, in Africa, Asia, Native North, central and South America and sidelines virtually every exhibition arena worldwide that is not based on an " Occidental " understanding of art and its appreciation. This is no serendipity : architecture generally speaking and museums in particular have played key roles in the construction of " first world " political, economic and cultural hegemonies ; such hegemonies, by definition, are the stuff of exclusion. With the foregoing observations as its point of departure and drawing on models developed outside the " Western " canon, this paper considers alternative approaches to museum design and, more fundamentally, to the very concept of the museum, as these might be experimented with in a contemporary African setting.
Keywords: African Research